Synthesis, characterization and evaluation of anti-dengue activity of enantiomeric Schiff bases derived from S-substituted Dithiocarbazate - Maryam, M.; Tan, Sang Loon *; Crouse, Karen A.; Mohamed Ibrahim, M. T.; Chee, H. Y. (Scientific Technical Research Council Turkey-Tubitak, 2020)
A series of Schiff bases have been successfully synthesized through the acid-catalyzed condensation of S-substituted dithiocarbazates and three enantiomerically pure monoterpenes, (1R)-(+)-camphor, (1S)-(-)-camphor, (1R)-(-)-camphorquinone, (1S)-(+)-camphorquinone, (R)-(-)-carvone and (S)-(+)-carvone. Spectroscopic results revealed that the Schiff bases containing camphor or carvone likely adopted an E-configuration along the characteristic imine bond while those containing camphorquinone assumed a Z-configuration.The anti-dengue potential of these compounds was evaluated based on DENV 2 caused cytopathic effect (CPE) reduction-based in vitro evaluation. The compounds were validated through secondary foci forming unit reduction assay (FFURA). Compounds were also tested for their cytotoxicity against Vero cells. The compounds showed variable degrees of antiviral activity with the camphor compounds displaying the highest anti-dengue potential. The enantiomers of the compounds behaved almost similarly during the antiviral evaluation.